Answer:
D 46x²+ 67x -16
Step-by-step explanation:
adding like terms
R1(x) + R2(x) = 16x²+52x-27 + 30x² + 15x + 11
total = 46x²+ 67x -16
The ratio 21:14 when divided by 7 on each side, is the smallest ratio that has the same value as 21:14. this becomes 3:2
then multiply both sides by a few different numbers on both sides each ,
for example, 3:2 is the same as
6:4 (3:2 times 2)
9:6 (3:2 times 3)
12:8 (3:2 times 4)
15:10 (3:2 times 5) and so on
the ratio of the right number I
divided by the left on all of them is 1.5
so,
14/10 equals 1.4 (nope)
8/4 equals 2 (nope)
9/6 equals 1.5 (yay)
12/21 equals 0.57 (Lol)
So your answer is 9:6
<span>Simplifying
x4 = 16
Solving
x4 = 16
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Simplifying
x4 = 16
Reorder the terms:
-16 + x4 = 16 + -16
Combine like terms: 16 + -16 = 0
-16 + x4 = 0
Factor a difference between two squares.
(4 + x2)(-4 + x2) = 0
Factor a difference between two squares.
(4 + x2)((2 + x)(-2 + x)) = 0
Subproblem 1
Set the factor '(4 + x2)' equal to zero and attempt to solve:
Simplifying
4 + x2 = 0
Solving
4 + x2 = 0
Move all terms containing x to the left, all other terms to the right.
Add '-4' to each side of the equation.
4 + -4 + x2 = 0 + -4
Combine like terms: 4 + -4 = 0
0 + x2 = 0 + -4
x2 = 0 + -4
Combine like terms: 0 + -4 = -4
x2 = -4
Simplifying
x2 = -4
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2
Set the factor '(2 + x)' equal to zero and attempt to solve:
Simplifying
2 + x = 0
Solving
2 + x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-2' to each side of the equation.
2 + -2 + x = 0 + -2
Combine like terms: 2 + -2 = 0
0 + x = 0 + -2
x = 0 + -2
Combine like terms: 0 + -2 = -2
x = -2
Simplifying
x = -2
Sub-problem 3
Set the factor '(-2 + x)' equal to zero and attempt to solve:
Simplifying
-2 + x = 0
Solving
-2 + x = 0
Move all terms containing x to the left, all other terms to the right.
Add '2' to each side of the equation.
-2 + 2 + x = 0 + 2
Combine like terms: -2 + 2 = 0
0 + x = 0 + 2
x = 0 + 2
Combine like terms: 0 + 2 = 2
x = 2
Simplifying
x = 2Solutionx = {-2, 2}</span>
It is B. Nikita used the wrong measurements when finding the area of the base. Please give a like. I Promise this is correct and if its not you can yell at me and all that! :)
Answer:
The question is incomplete. The complete question and its solution is attached below: